Prevalence and influencing factors of Chlamydia trachomatis, Neisseria gonorrhoeae and Treponema pallidum infection among men who have sex with men in Yunnan province, 2020: a cross-sectional survey - Yan GUO; Xiao ZHANG; Chao-jun YANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo investigate the prevalence and influencing factors of Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG) and Treponema pallidum (TP) infection among men who have sex with men (MSM) in Yunnan province for providing evidence to develop strategies on sexually transmitted infection prevention and control.MethodsTotally 1 400 MSM aged 15 - 65 years and with insertive oral or anal sex during past one year were recruited with snowball sampling in 14 prefectures/cities of Yunnan province in 2020. Face-to-face questionnaire interview, sampling of b1ood, urine, and pharyngeal/rectal swab specimens for tests of CT, NG and TP infection were carried out among the MSM. Logistic regression model was adopted in analyses on influencing factors of the infections. ResultsAmong the 1 298 MSM with valid information, the detection rates were 9.9% (number of positive cases: 129), 3.1% (40) and 3.2% (42) for CT, NG and TP infection, respectively, with the highest positive rate (6.0%, 61/1 023) of CT infection for rectal swab specimens and that (1.8%, 22/1 190) of NG infection for pharyngeal swab specimens. The results of multivariate logistic regression analysis showed that the MSM living in central region (odds ratio [OR] = 4.217, 95% confidence interval [95% CI]:1.611 - 11.04) or northwestern region (OR = 3.521, 95% CI：1.357 - 9.136) compared to living in northeastern of the province and the MSM with the education of junior high school and below (versus college and above: OR = 2.333, 95% CI：1.427 - 3.813) were more likely to have CT infection; the results also revealed that with the education of junior high school and below (versus college and above: OR = 2.935, 95% CI：1.265 - 6.812) and seeking sexual partners via internet/dating applications (versus through other routes: OR = 2.64, 95% CI： 1.019 - 6.836) were risk factors for NG infection, and suffering from sexually transmitted diseases in past one year was a risk factor (OR = 43.983, 95% CI：19.31 - 100.182) for TP infection. ConclusionAmong MSM in Yunnan province, the prevalence of CT, NG and TP infection were relatively high, suggesting that comprehensive intervention measures, including screening on the infections among high-risk individuals, should be strengthened in the MSM.